Membangkitkan Indonesia: Koalisi Antar-Agama Melawan Korupsi dan Kemiskinan - Zuly Qodir (Unisia, 2004)
Religion as a source of our rule and guidance shows us the good from the bad, the truth from the false. Our recent problem, especially in Indonesia is an opinion that corruption seems not as a crime. As a part of a nation, as NGO, government, all people have to declare that corruption is a crime and corruptor is a criminal offender. The better Interpretation should be made for Internalizing religious values to the people, because so far, good knowledge about religion doesn't mean the ability to prevent someone from corruption. We should together build a system which strictly prevents us from corruption from the small to the bigger level, not just through moral prevention but also using very strict legal system to overcome this problem.